A Textual and Pedagogical Analysis of Muqaddimah fī Ta‘līmi wa Ta‘allumi at-Taṣrīf by Abd al-Bāsiṭ - David Arif Prayogi; Dedy Irawan; Afif Amrullah; Safari Daud (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2026)
This study aims to analyze the variety of wazan sighat isim fā‘il tsulāthī mujarrad presented in the book Pengantar Belajar Mengajar Tashrif by KH. Abdul Basith and examine its pedagogical implications for Arabic morphology learning. The research addresses the phenomenon of limited understanding in many Islamic educational institutions that restrict isim fā‘il to a single pattern, despite the existence of broader variations in classical sharaf theory. This study employed a qualitative approach using library research design. Data were collected through documentation techniques by examining the primary text of KH. Abdul Basith’s book, supported by classical sharaf references and contemporary linguistic studies. The data were analyzed through classification, comparison, and interpretation of the identified wazan patterns based on classical morphological principles. The findings reveal that the book presents diverse wazan forms of isim fā‘il, such as فَاعِلٌ، فَعِلٌ، فَعِيْلٌ، فَعْلَانُ، أَفْعَلُ, and فَعَلٌ, which generally align with classical sharaf rules and reflect distinct semantic nuances such as permanence, intensity, and temporary states. These findings contribute to a deeper understanding of Arabic morphological richness and emphasize the importance of integrating structural and semantic dimensions in teaching sharaf. The study implies that Arabic learning materials should adopt a more comprehensive approach to wazan variation to enhance students’ conceptual mastery. Further research is recommended to explore the practical implementation of these patterns in classroom settings and their impact on students’ linguistic competence.